Use of, and likelihood of using, HIV pre-exposure prophylaxis among men who have sex with men in Europe and Central Asia: findings from a 2017 large geosocial networking application survey. (5th January 2019) - Bourne, Adam; Alba, Beatrice; Garner, Alex; Spiteri, Gianfranco; Pharris, Anastasia; Noori, Teymur
Abstract : Objective: Currently, seven European countries provide HIV pre-exposure prophylaxis (PrEP) through public health services, although there are numerous reports of off-licence use. The objective of this study was to examine current use of PrEP, likelihood of future use and indicators of potential PrEP candidacy among an opportunistic sample of men who have sex with men in Europe and Central Asia. Methods: A survey was sent out in eight languages to users of the Hornet gay networking application in July and August 2017. Descriptive statistics present proportions of PrEP use, while factors associated with PrEP use are examined using logistic and linear regressions. Results: Of 12 053 participants whose responses came from 55 European and Central Asian countries, 10 764 (89%) were not living with diagnosed HIV. Among these HIV-negative/untested men, 10.1% (n=1071) were currently taking PrEP or had done so within the previous 3 months. Current or recent PrEP users were significantly more likely to have taken postexposure prophylaxis (adjusted OR (AOR)=16.22 (95% CI 13.53 to 19.45)) or received an STI diagnosis (AOR=4.53 (95% CI 3.77 to 5.44)) in the previous 12 months than those who had not. Most commonly, these men obtained PrEP from a physician (28.1%) or the internet (24.8%), while 33.6% had not disclosed PrEP use to their doctor. Men reporting happiness with their sex life were more likely to have taken PrEP (AOR=1.73 (95% CI 1.59 to 1.89)). Nearly a quarter (21.5%) of those not on PrEP said they were likely to use it in the next 6 months. Conclusions: The majority of men using, or intending to use, PrEP appear to have a risk profile consistent with emerging guidance. A large proportion of these men are accessing PrEP outside of traditional healthcare settings, posing a challenge for routine monitoring.